A Sociological Study on the Effect of Virtual Social Networks on Generation Gap: a Case Study of Shiraz University Students - esrafil javidi; habib ahmadi; mahrokh rajabi (توسعه اجتماعی)
The generational gap means the existence of differences in the knowledge, attitudes and behavior between the two generations of youth and adults, especially in the aspect of identity; it affects every society in a broader way in the social and cultural structures. In a way that identity, sense of belonging to the culture, value and culture of the native in generations, which provides the social solidarity of a society, causes difference, cultural conflict and identity. The research was carried out using a survey method using a questionnaire technique. All students who studied at Shiraz University in undergraduate and higher education in the first half of the academic year 2018-2019 in Shiraz have formed the statistical population of this study. Sampling in the present study is based on stratified sampling. The sample size was 386 people based on Cochran formula. The findings of the research show that there is a significant positive relationship between the variables of the use of virtual social networks, the history of using virtual social networks and the level of satisfaction with virtual social networks with the generation gap. The results of structural equations show that the variables of virtual social networks, cultural capital and social capital have a significant effect on the generation gap, and the magnitude of this effect is 1.02, -0.022 and -0.0923.